1998
DOI: 10.1002/(sici)1521-4109(199804)10:4<223::aid-elan223>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Pyranose Oxidase Modified Carbon Paste Electrodes for Monosaccharide Determination

Abstract: An amperometric biosensor for the detection of some monosaccharides was developed with co-immobilized pyranose oxidase (purified from the basidiomycete fungus Phanerochaete chrysosporium) and horseradish peroxidase in carbon paste. Due to rather low selectivity of pyranose oxidase, the biosensor could detect both predominating anomers of D-glucose as well as the substrates D-xylose, D-galactose, and d-gluconolactone. The best sensor performance was obtained from a carbon paste with covalently immobilized enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 62 publications
1
20
0
1
Order By: Relevance
“…POx was also shown to have high activity for saccharides such as sorbose, and mannose [24]. Besides the regioselective oxidation of a number of pyranose sugars at position C-2, POx also acts on C-3 of certain substrates such as 2-deoxy-d-glucose, 2-keto-d-glucose and methyl ␤-d-glucosides [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…POx was also shown to have high activity for saccharides such as sorbose, and mannose [24]. Besides the regioselective oxidation of a number of pyranose sugars at position C-2, POx also acts on C-3 of certain substrates such as 2-deoxy-d-glucose, 2-keto-d-glucose and methyl ␤-d-glucosides [22].…”
Section: Introductionmentioning
confidence: 99%
“…Since its first characterization by Janssen and Ruelius, POx has received attention as the key biocatalysts in various biotechnological applications; especially analytical applications in clinical chemistry, in monitoring industrial processes, in food preservation and in synthetic carbohydrate chemistry [25][26][27][28][29]. POx has also been used as a biological component in biosensor [18,19,24,27,[30][31][32][33][34][35]. Despite the large-scale industrial use of GOx, there are two main potential advantages in using POx instead of GOx.…”
Section: Introductionmentioning
confidence: 99%
“…Pyranose dehydrogenase (PDH) from Agaricus meleagris can also oxidize glucose at the C-2 and C-3 positions [67]. In 1997, Lidén et al reported PyOx-modified carbon paste electrodes that served as a biosensor interface to test a series of monosaccharides [68]. Since that time, several studies on the use of PyOx as an anodic BFC catalyst have been reported [69,70].…”
Section: Promiscuous Enzymes For Glucose Anodesmentioning
confidence: 99%
“…These studies show that the use of charged polyelectrolytes with various charge densities, molecular weights and sizes, allow for the formation of a very efficient, tightly bound imprinting cover around the enzyme. Even though polyelectrolytes have been used extensively for the stabilization of enzymes, for example lactate oxidase [78], tyrosinase [79,80] fructose dehydrogenase [24], oligosaccharide dehydrogenase [81], pyranose oxidase [82], pyruvate oxidase [83], catalase when used in an organic solvent system [75,78,81,83,84,85,86,87,88,89,90], and many more, their application to the development of biosensors is very limited indeed.…”
Section: Polyelectrolytes For Enzyme Stabilizationmentioning
confidence: 99%